2015
DOI: 10.2146/ajhp150077
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted approach to reducing occurrence of severe hypoglycemia in a large healthcare system

Abstract: A multifaceted, evidence-based, data-driven approach enabled a large healthcare system to markedly reduce the frequency of severe hypoglycemia events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Of the five time series studies, Coleman et al 18 identified a 0.41% decrease in missed doses of medications other than antibiotics (p=0.007); however, it was part of four concurrent interventions to reduce missed and delayed medication doses, and thus, the specific impact of the dashboard was unclear. Similarly, Milligan et al 41 reported a reduction in hypoglycaemic rates, Rioux et al 28 reported a decrease in surgical site infections over a 6-year period after dashboard implementation, and Mackie et al 35 reported a reduction in hospital-acquired pressure ulcers; however, in each case, the dashboard was one aspect of a broader campaign to reduce the respective patient safety events. Other studies, including Bakos, Chandraharan, Collier, Conway, Hebert, Hendrickson and Hyman, 15 17 22 24 25 30 37 reported a subjective reduction in patient safety events, but did not describe a statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of the five time series studies, Coleman et al 18 identified a 0.41% decrease in missed doses of medications other than antibiotics (p=0.007); however, it was part of four concurrent interventions to reduce missed and delayed medication doses, and thus, the specific impact of the dashboard was unclear. Similarly, Milligan et al 41 reported a reduction in hypoglycaemic rates, Rioux et al 28 reported a decrease in surgical site infections over a 6-year period after dashboard implementation, and Mackie et al 35 reported a reduction in hospital-acquired pressure ulcers; however, in each case, the dashboard was one aspect of a broader campaign to reduce the respective patient safety events. Other studies, including Bakos, Chandraharan, Collier, Conway, Hebert, Hendrickson and Hyman, 15 17 22 24 25 30 37 reported a subjective reduction in patient safety events, but did not describe a statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of "bundled" preventative therapies including proactive surveillance of glycemic outliers and an interdisciplinary data-driven approach to glycemic management showed that hypoglycemic episodes in the hospital could be prevented. Compared with baseline, two such studies found that hypoglycemic events fell by 56% to 80% (49,50). The Joint Commission recommends that all hypoglycemic episodes be evaluated for a root cause and the episodes be aggregated and reviewed to address systemic issues.…”
Section: Preventionmentioning
confidence: 99%
“…Studies of "bundled" preventative therapies including proactive surveillance of glycemic outliers and an interdisciplinary data-driven approach to glycemic management showed that hypoglycemic episodes in the hospital could be prevented. Compared with baseline, two such studies found that hypoglycemic events fell by 56% to 80% (38,39). The Joint Commission recommends that all hypoglycemic episodes be evaluated for a root cause and the episodes be aggregated and reviewed to address systemic issues.…”
Section: Preventionmentioning
confidence: 99%